Protective effects of simvastatin against ultraviolet B-induced photoaging of human dermal fibroblasts - Oktarina, Dyah Ayu Mira; Iqbal, Roihan Mohamad (Iranian Society of Dermatology, 2022)
Background: Simvastatin is a beta-hydroxy-beta-methylglutaryl- CoA (HMG-CoA) inhibitor molecule with several pleiotropic (immunomodulatory, anti-inflammatory, and antioxidant) activities. In this study, we evaluated the protective effect of simvastatin on ultraviolet B (UVB)-induced photoaging of normal human dermal fibroblast cultures by assessing fibroblast proliferation, collagen deposition, and fibroblast morphology.